Result of reptile and frog investigations in some areas of West-South Vietnam and neighbouring islands - Sang, Nguyen Van; Cuc, Ho Thu (Academia Journal of Biology, 2013)
Result of reptile and frog investigations in some areas of West-South Vietnam and neighbouring islands